Bank Equity Stakes in Borrowing Firms and Financial Distress - Berlin, Mitchell; John, Kose; Saunders, Anthony (Review of Financial Studies, 1996)
We derive the optimal financial claim for a bank when the borrowing firm’s uninformed stakeholders depend on the bank to establish whether the firm is distressed and whether concessions by stakeholders are necessary. The bank’s financial claim is designed to ensure that it cannot collude with a healthy firm’s owners to seek unnecessary concessions or to collude with a distressed firm’s owners to claim that the firm is healthy. To prove that a request for concessions has not come from a healthy firm/bank coalition, the bank must hold either a very small or a very large equity stake when the firm enters distress. To prove that a distressed firm and the bank have not colluded to claim that the firm is healthy, the bank may need to hold equity under routine financial conditions.